No association of the SNP rs1048261 within 3'UTR of HSPB7 with cardiovascular morbidity in patients with psoriasis; a possible effect on miRNA-mediated translational regulation. (2016) - , Pavel Hruska*; Zlamal, Filip; ,; Vasku, Vladimir; Bienertova-Vasku, Julie
No abstract available